1990
DOI: 10.1002/1097-0142(19900315)65:6<1273::aid-cncr2820650603>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity correlation between the primary tumors and simultaneous metastatic lymph nodes of patients evaluated by DNA synthesis inhibition assay

Abstract: The chemosensitivities of primary tumors (PT) and simultaneous metastatic lymph nodes (MN) to mitomycin C (MMC), 5-fluorouracil (S-FU), Adriamycin (ADR) (doxorubicin; Adria Laboratories, Columbus, OH), carboquone (CQ), or cisplatin (CDDP) were assessed in a group of 29 patients (11 gastric, 8 colorectal, 4 breast, and 6 other cancers) by a DNA synthesis (3H-thymidine incorporation) inhibition assay. PT and MN from the same patient showed heterogeneity in chemosensitivity. MN were more sensitive to the agents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In this model, however, up-regulation of DPD occurred during liver metastases. It became widely accepted that tumors were heterogeneous, and cells from individual tumors differed in biologic characteristics, cellular morphology, karyotype, growth rate, receptors, metabolism, and metastatic ability, even if tumors derived from one patient have the same origin or history (16). Studies have stated that some tumors arise from a small population of 'cancer stem cells,' which may be more resistant to chemotherapy and cause metastases (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, however, up-regulation of DPD occurred during liver metastases. It became widely accepted that tumors were heterogeneous, and cells from individual tumors differed in biologic characteristics, cellular morphology, karyotype, growth rate, receptors, metabolism, and metastatic ability, even if tumors derived from one patient have the same origin or history (16). Studies have stated that some tumors arise from a small population of 'cancer stem cells,' which may be more resistant to chemotherapy and cause metastases (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the rRNA bands was checked using agarose gel electrophoresis. Prepared total RNA (1 μg) was reverse-transcribed to synthesize cDNA using the oligo(dT) [12][13][14][15][16][17][18] primer and Superscript II (Invitrogen, Inc, Carlsbad, CA) according to the manufacturer's instructions. Expression levels of TS, DPD, TP, OPRT, and UP mRNA were measured by real-time quantitative RT-PCR (LightCycler; Roche Diagnostics GmbH, Mannheim, Germany) and LightCycler mRNA Quantification Plus kit for TS, DPD, and TP mRNA (Roche Diagnostics GmbH) according to the manufacturer's instructions.…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chaimentioning
confidence: 99%
See 1 more Smart Citation
“…The [ 3 H]-uridine incorporation into RNA was achieved similar to the incorporation of [ 3 H]-thymidine into DNA except that 1 h before harvesting the cells, 1 ACi of [ 3 H]-uridine has been added to each well (Hall et al, 1982). The extent of inhibition of DNA and RNA synthesis were determined by the following equation: %inhibition = [1-test (cpm)]/[control (cpm)] Â 100 (Nio et al, 1990;Nio et al, 2000).…”
Section: Inhibition Of Nucleic Acids Biosynthesismentioning
confidence: 99%
“…The heterogeneity of chemosensitivity among the tumor cells derived from the same organ, or that between the primary and metastatic tumors in the same patient is thought to be one of the causes responsible for unsuccess-ful chemotherapy [22,23]. Clinical experience suggests that tumor cells from different lesions of the same patient show different chemosensitivity, and some reports have demonstrated this phenomenon in vitro [24,25], We have already demonstrated that metastatic tumors were more sensitive than primary tumors in patients with gastric or colorectal cancer by our results from a DNA synthesis inhibition assay [19]. The present study also showed that although only VP-16 was effective for primary pancreatic cancer, EPIR and CQ were effective for metastasis of pancreatic cancer as well and that metastasis of pancreatic cancer, except skin metastasis, was more sensitive than primary pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%